Community Collaboration in Public Health Genetic Literacy: Methods for Co-Designing Educational Resources for Equitable Genomics Research and Practice - Juhi Salunke; Grace Byfield; Sabrina N. Powell; Daniel F. Torres; Grace Leon-Lozano; Jahnelle Jackson; Andreas K. Orphanides; Jonathan Shaw; Thomas Owens; Jonathan S. Berg; Elizabeth Branch; Lennin Caro; et al. (Public Health Genomics)
Introduction: Unequal representation in genetic and genomic research is due to various factors, including historically inequitable and unjust institutional research practices, potential mistrust of biomedical research among underrepresented populations, and lack of access to or awareness of research opportunities. Facilitating sustainable dialog between diverse communities and genetic researchers can cultivate trusting, bidirectional relationships, potentially encouraging greater participation in research. Herein, we describe the co-creation of public health educational materials and dissemination plans using an approach designed to address inequities and foster community dialog. Methods: In this Methods article, we describe the iterative co-creation of genetics and genomics educational modules by genetics clinicians, researchers, and community members. The goal of these modules is to enhance the genetic literacy of the lay population and to facilitate informed decision-making regarding genetic research and health services. We used Designing for Dissemination and Sustainability, grounded in Dissemination and Implementation science, and its Fit to Context process framework to guide the process. This approach ensures that the public health context and writing for a diverse audience are considered throughout the modules’ development. Conclusion: This article offers an evidence-based template for adoption or adaptation by other community-engaged groups, aimed at bolstering equity and sustainability in the development of healthcare interventions and with an emphasis on accessible public health literacy. The co-creation by researchers and community members of both materials and dissemination plans may improve the cultural appropriateness and relevance of public health genetics campaigns. Ongoing research is needed to assess the impact of this approach on receptiveness and participation.